As metodologias ativas na formação inicial de professores de Ciências e Biologia: um olhar para os estágios curriculares supervisionados - Machado, Jeniffer Sabrina (2022)
Active methodologies present themselves as a teaching model with the potential to move towards a more flexible and student-centered curriculum, making them the protagonist and main agent of their learning process. In this context, teacher training can act as a catalyst or limit for immersion in this innovative model. In order to deepen the understanding of active methodologies and teacher training, this exploratory bibliographic, documentary and field work sought to answer the following question: What do the documents of initial teacher training, the reports of Supervised Internships and do the Science and Biology interns show us about the use of active methodologies in teacher training? The objective of this research sought to establish indications on the use of active methodologies by Science and Biology interns in elementary school, final years and high school, observing the results of two higher education institutions in the western region of the state of PR. For data constitution and analysis, Discursive Textual Analysis (DTA) was used, with three categories of analysis being constructed: I. Active methodologies as an alternative to traditional teaching, II. Active methodologies and the role of the student and the teacher in teaching and learning, III. Active methodologies in the initial training of Science and Biology teachers. Through the studies carried out, it was possible to verify that the Pedagogical Course Projects (PPC) of the two educational institutions do not address the topic of active methodologies in their content. In addition, the answers of the interns of the Degree in Biological Sciences of the year 2019 to the questionnaire indicate that they consider they have studied active methodologies at some point in the course, and the vast majority indicated that they had used these during the supervised internships of sciences. and Biology. However, the Supervised Internship reports indicate that the interns predominantly used traditional teaching, where expository classes, dialoged expository and dialogic discursive classes appeared as a highlight in the lesson plans. Regarding the use of active methodologies, the inverted classroom was the most used, followed by Group/Team Learning (TBL) and Gamification, but in a timid and punctual way. Thus, the results show us contradictions between the discourse and the practice of the trainees regarding the use of active methodologies in teaching practice, which made us infer that the training offered by the Degree courses in Biological Sciences of the two universities, in relation to the theme active methodologies, presents elements of fragility insofar as aspects of dichotomy between theory and practice appear in the analyzed data. From this, we need to move towards more significant reflections in relation to the path to be followed for the implementation of active methodologies in teaching practice, even if it is a path marked by difficulties and barriers, however, it is important to remember that obstacles and adversities are present in any innovation process and that moving forward, returning, choosing new paths and continuing the journey is part of a successful trajectory in any area